2018
DOI: 10.5295/cdg.140515ss
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between entrepreneur’s traits and cloud computing adoption among malay-owned SMEs in Malaysia

Abstract: Purpose of the research: This research aims to empirically examine the relationship between entrepreneurs' personality traits and cloud computing adoption among Malay-owned SMEs in Malaysia. The research was done under theoretical framework that was developed based on the previous literature.Methodology: This study adopts non-probability sampling which is convenient sampling for data collection. Data collection was done in all major towns in West Malaysia. Hypotheses related to personality factors (determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…The use and diffusion of information and communication technologies (ICTs), in transforming society in general and commercial organisations in particular, have given rise to so-called "information societies" [1]. Consequently, research on adopting ICTs has aroused great interest among scholars in various fields, especially business [2][3][4]. To date, such studies have shown ICTs' contribution to the competitive advantage of organisations that have implemented them in terms of their productivity [5], internationalisation [6,7], performance in the labour market [8] and ability to continue being competitive [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The use and diffusion of information and communication technologies (ICTs), in transforming society in general and commercial organisations in particular, have given rise to so-called "information societies" [1]. Consequently, research on adopting ICTs has aroused great interest among scholars in various fields, especially business [2][3][4]. To date, such studies have shown ICTs' contribution to the competitive advantage of organisations that have implemented them in terms of their productivity [5], internationalisation [6,7], performance in the labour market [8] and ability to continue being competitive [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Perceived compatibility is defined as the extent to which m-commerce transaction is consistent with the existing technology infrastructure, culture, values, and preferred work practices of SMEs. Most of the earlier research on perceived compatibility and adoption has been demonstrated and approved (Alam et al, 2018). Therefore: H5: There is a positive significant relationship between perceived compatibility and m-commerce adoption.…”
Section: Perceived Compatibilitymentioning
confidence: 96%
“…La adopción de las Tecnologías de la Información y la Comunicación (TIC) sigue despertando importante interés en diferentes contextos, entre ellos el empresarial (Alam, Nor, Ali, Omar, & Wel, 2017;Bresnahan & Yin, 2016). La literatura ha ofrecido evidencias de la contribución de estas tecnologías a los resultados competitivos de las organizaciones que las implantan, existiendo una amplia bibliografía que aborda desde el carácter de "commodity" (Carr, 2004) hasta la importancia de las mismas a pesar de su aparente homogeneidad (Piccoli & Lui, 2014).…”
Section: Introductionunclassified